PERSEPSI PETANI TERHADAP PENGEMBANGAN KEDELAI HITAM DI PLAYEN 133 - 144 GUNUNG KIDUL - Yulianto, Gunawan (Jurnal Ilmu-Ilmu Pertanian, 2005)
This research was aim for describing the farmer perception about black soybean and its realization, and also get the pictures about the factors that influence it by factual. This research used qualitatif-naturalistic approach, collecting data have the character of descriptive in the form of words. This research was counducted in Playen Gunung Kidul in November 2004. The result of research showed that there was no different between yellow soybean and black soybean, in the case of its technical cultivation. Farmers have experiences of soybean planting, so that there was no constraint about black soybean development. The black soybean development constraint emerged from farmer perception which saw that black soybean is difficult to market especially in large quantity, there was no certain market and its price lower than yellow soybean, so that farmer didnt make profit. Factors which were the background of farmer perceptions and influenced the accuracy of perception were internal condition of farmer like farm experience, education / training experience, age, and the condition of farmer external like certainty of price and market. The implication of this research is to develop black soybean need the existence of certainty of market at the equal price with yellow soybean. To change the farmer perception about black soybean, there should be extension action especially about making added value to the farmer. There also should be cooperation, among local government of Gunungkidul, STPP BPTP and other related institution in order to empower the farmer